2001
DOI: 10.1111/0161-4681.00120
|View full text |Cite
|
Sign up to set email alerts
|

An Uncertain Lever: Exploring the Influence of State-Level Testing in New York State on Teaching Social Studies

Abstract: In this paper, the author presents case studies of two high school social studies teachers and the influence of state-level testing on their teaching practices. Based on classroom observations of a unit on the U.S. civil rights movement and teacher interviews before and after that unit, he examines the role the eleventh grade New York State Regents test in U.S. History and Government plays in each teacher's instructional planning, delivery, and assessment. His analysis suggests that while the state test figure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…These studies will be examined in this article. (Grant, 2001) change as activity and difference vs. change as improvement (Corbett & Wilson, 1991) and teachers as policybrokers vs. teachers as implementors (Schwille et al, 1983), emerged as key to the second level of analysis. All of these ideas and phrases prompted consideration of two types of policy: teacher policy and external policy.…”
Section: Selection and Analysis Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…These studies will be examined in this article. (Grant, 2001) change as activity and difference vs. change as improvement (Corbett & Wilson, 1991) and teachers as policybrokers vs. teachers as implementors (Schwille et al, 1983), emerged as key to the second level of analysis. All of these ideas and phrases prompted consideration of two types of policy: teacher policy and external policy.…”
Section: Selection and Analysis Of Literaturementioning
confidence: 99%
“…Some of the research, on the other hand, suggests that the influence of state-mandated testing is overstated and limited (Firestone, Mayrowetz, & Fairman, 1998;Glasnapp, Poggio, & Miller, 1991;Grant, 2000Grant, , 2001Zancanella, 1992). These researchers posit that the influence of state tests and/or testing programs-as motivators of curricular and instructional reform at the local level-may be non-existent or of very low intensity.…”
Section: The Overstated and Limited Influence Of State-mandated Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…In his study of New York teachers' perceptions of changes in their state's testing program, S.G. Grant (2001) reviewed the literature on the relationship between high stakes test scores, professional development and classroom instruction. Grant found that few empirical studies represent the relationship between instruction and the tests they administer.…”
Section: Research Into the Impact Of High Stakes Testing On Classroommentioning
confidence: 99%